FACEBOOK SEBAGAI MEDIA PROMOSI MASJID BERBENTUK KA’BAH PONPES DARUSSALAM PUNCAK BARUREJO SILIRAGUNG BANYUWANGI - Maskur Maskur; Abdul Aziz; Khotibul Umam; Amrul Masduki (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study examines the strategy of da'wah in the media of facebook, because along with the times, the da'i use facebook as a medium in conveying the symbols of Islam, with the existence of this media, messages will be conveyed quickly to the general public. The question in this research is how the strategy of Da'wah through Facebook is carried out by the preacher at the Darussalam Islamic Boarding School, Puncak Banyuwangi. not only used as a place of prostration (prayer) only. Especially for performing the five daily prayers, Friday prayers, and other worship, it is also used for Islamic syiar activities, religious education, training and social activities. The Kaaba Puncak Syafa'at Mosque in the form of the Kaaba in the Darussalam Islamic Boarding School Puncak Banyuwangi, is expected to be able to become a center for Islamic activities as well as Syiar and Da'wah in the form of education such as PAUD, TK, SD and SMP and TK-TP Al-Qur'an.